1995
DOI: 10.1002/art.1780380607
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between gold‐induced enterocolitis and the presence of the HLA‐DRB 1*0404 allele

Abstract: Objective. In recent years we have treated 4 rheumatoid arthritis (RA) patients who developed goldinduced enterocolitis, a well‐recognized, although rare, complication of chrysotherapy. The aim of the present study was to seek any genetic predisposition for this complication. Methods. HLA DNA typing was done on fresh white blood cells from the 4 patients. Results. Three of the 4 patients (75%) exhibited the DRB 1*0404 allele, whereas the prevalence of this allele among the Ashkenazi Jewish population of RA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…DNA typing of HLA-DR alleles from patients with RA confirmed the shared epitope hypothesis, because HLA-DRB1*0401, 0404, 0405, 0408, HLA-DRB1*0101 and DRB1*1402 share the same sequence at positions 70–74 in the third exon, but DRB1*0402 and others do not [7, 14]. HLA antigens have also been reported to be associated with the reactive side effects of drugs to RA [15, 16, 17, 18, 19, 20, 21]and also with the severity of the disease [22, 23, 24, 25, 26, 27, 28, 29, 30]as well as with the susceptibility to RA with extra-articular manifestations [25, 31, 32, 33, 34, 35]. …”
Section: Introductionmentioning
confidence: 57%
“…DNA typing of HLA-DR alleles from patients with RA confirmed the shared epitope hypothesis, because HLA-DRB1*0401, 0404, 0405, 0408, HLA-DRB1*0101 and DRB1*1402 share the same sequence at positions 70–74 in the third exon, but DRB1*0402 and others do not [7, 14]. HLA antigens have also been reported to be associated with the reactive side effects of drugs to RA [15, 16, 17, 18, 19, 20, 21]and also with the severity of the disease [22, 23, 24, 25, 26, 27, 28, 29, 30]as well as with the susceptibility to RA with extra-articular manifestations [25, 31, 32, 33, 34, 35]. …”
Section: Introductionmentioning
confidence: 57%
“…Four Jewish female RA patients who developed goldinduced enterocolitis, were examined for possible genetic predisposition [99]. Results indicated that the DRB1*0404 allele -present in 3 of the 4 patients -may be associated with risk for development of gold-induced enterocolitis.…”
Section: Enterocolitismentioning
confidence: 99%
“…Results indicated that the DRB1*0404 allele -present in 3 of the 4 patients -may be associated with risk for development of gold-induced enterocolitis. Because the prevalence of this allele among the middle and northern European Jewish populations of RA patients without colitis was 9.2 %, authors concluded that HLA DNA typing should be considered in Jews who are contemplating chrysotherapy [99].…”
Section: Enterocolitismentioning
confidence: 99%
“…Among the more unusual forms of macroscopic colitis are those caused by methotrexate and gold. In gold- induced colitis peripheral eosinophilia is observed in about 25% of the cases [54, 55]. Gold colitis should be suspected in rheumatoid arthritis patients treated with either oral or parenteral gold.…”
Section: Rare Forms Of Colitismentioning
confidence: 99%